An investigation of the properties of nuclear levels by nuclear orientation - Dagley, P (1959)
Nuclear alignment has been on established technique in nuclear physics for some years and the majority of the experiments have employed the methods suggested by Bleaney (1951) and by Rose (1949) and Gerter (1948). The former is simpler since it requires no external fields. For this method the nucleus must be the core of a paramagnetic ion which is included in a crystal with suitable internal fields. The alignment arises through anisotropic hyperfine structure (S(off)=[illegible fraction]) or isotropic hyperfine structure with a finite splitting of the electronic levels caused by the crystalline field (D≠OS≥1). Certain nuclear states will become predominantly populated at very low temperatures which can conveniently be produced by adiabatic demagnetisation of an ion incorporated in the same salt. Paramagnetism arises through vacancies in the 3f and 4d electronic shell so that those nuclei studied fall in the iron-transition and rare-earth groups. The former can be conveniently incorporated with the salts of the Tutton series (double sulphates) or the double nitrates, both of which have been extensively studied. However, the Tutton salts have two ions per unit cell giving rise to two alignment axes inclined at about 70° while for some of the iron group elements (e.g. Co++, Mn++) the double nitrates have two positions in the unit cell with different hyperfine constants Following the successful cooling of nickel-zinc fluosilicate by adiabatic demagnetisation (Hill, Meyer & Milner 1959) it was realised that this salt which has one ion per unit cell might be suitable for nuclear orientation and indeed have some advantages over the other salts. All the principal experiments described in this thesis have been performed with nickel-zinc fluosilicate. The angular distribution of the gamma-radiation from an aligned nucleus is not in general isotropic, the anisotropy depending on the degree of alignment and decay characteristics of the isotope. Thus by measuring the anisotropy it is possible to deduce values for some of the nuclear parameters such as the angular moments and magnetic moment of the levels involved. [This is the start of the abstract. For the full abstract, please consult the PDF.]